What Derives Economic Growth at State Level? The Role of Personal Income Tax, VAT, Federal Allocation And Debt - Emmanuel John Kaka (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2021)
ABSTRACT  The main aim of the study is to assess the impact of personal income tax, Value Added Tax, debt and federal allocation on economic growth at state level in Nigeria. Expo factor research design was used. Secondary data were collected from Central Bank of Nigeria statistical bulletin and Debt Management office and Bureau of statistics from 1960 to 2019. Ordinary Least Square multiple regression method was used in data analysis. The results of the study showed that domestic debt and total expenditure where discovered to be positive and to have a significant influence on Gross Domestic Product. Similarly, foreign debt was also discovered to be positive and statistically significant on Gross Domestic Product. While, Value Added Tax was discovered to be positive and have insignificant effect on Gross Domestic Product. While, Personal Income Tax, federation account is discovered to be negative and the relationship between them are also not statistically significant and so the impact of Personal Income Tax and federation account are weak. The study concluded that most of the developmental activities that leads to the growth of Gross Domestic Product are being funded through debt (both domestic debt and foreign debt).